1977
DOI: 10.46429/jaupr.v61i2.10458
|View full text |Cite
|
Sign up to set email alerts
|

Título en español.

Abstract: Two experiments were conducted to evaluate the effectiveness of three nematicides in the control of nematodes that affect plantain (Musa acuminata x M. balbisiana, AAB): one at the Corozal Agricultural Substation and the other at the Gurabo Substation. The results show that all of the three doses of Dasanit 15G. Mobcap 10G, and Furadan 10G tested were effective in controlling nematodes, increasing yield, and extending the useful life of the plantation so that three crops were harvested without renovating the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…Although, it is difficult to determine the damage caused by a specific nematode species in banana, nematicide application provided 61 to 98% yield increase with root-knot and spiral nematode infestation in Nigeria (Caveness & Badra, 1980;Badra & Caveness, 1983) and Ivory Coast (Adiko, 1988). Also, it was reported that nematicides gave 119% and higher yield increases in the banana plantations in Jamaica (Hutton & Chung, 1973) and in Puerto Rico, nematicides gave 207-275% yield increases for more than 3 years (Roman et al, 1977). A yield loss of 15-50% due to R. similis and H. multicinctus was reported in East Africa (Speijer & De Waele, 2001).…”
Section: Resultsmentioning
confidence: 96%
“…Although, it is difficult to determine the damage caused by a specific nematode species in banana, nematicide application provided 61 to 98% yield increase with root-knot and spiral nematode infestation in Nigeria (Caveness & Badra, 1980;Badra & Caveness, 1983) and Ivory Coast (Adiko, 1988). Also, it was reported that nematicides gave 119% and higher yield increases in the banana plantations in Jamaica (Hutton & Chung, 1973) and in Puerto Rico, nematicides gave 207-275% yield increases for more than 3 years (Roman et al, 1977). A yield loss of 15-50% due to R. similis and H. multicinctus was reported in East Africa (Speijer & De Waele, 2001).…”
Section: Resultsmentioning
confidence: 96%
“…R. similis вважається найбільш небезпечним шкідником в районах вирощування бананів. Дослідження показали, що тільки застосування нематоцидів проти цього паразита дозволило підвищити врожайність бананів на 86 % -у Панамі, 15 % -у Гондурасі [168], 207-275 % -в Пуерто-Рико (протягом 3-х років застосування) [169], 5-30 % -в Австралії, 71 % -в Еквадорі, 267 % -у Сент-Вінсенті [170,171], 38 % -у Південній Африці [172], 16-263 % -у Кот-д'Івуарі [170,173], 20-40 % -у Камеруні [174,175], 35-40 % -на Мадагаскарі [176], 29-35 % -на Мартиніці [170] та на 46 % -в Cент-Люсії [170,177].…”
Section: результати дослідженняunclassified